2014
DOI: 10.5039/agraria.v9i4a4560
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de plantas de Bauhinia cheilanta micorrizadas em dois tipos de solo do bioma Caatinga

Abstract: RESUMOA aplicação de fungos micorrízicos arbusculares (FMA) em plantas forrageiras pode contribuir para maior produção de biomassa porém seu uso deve preceder o conhecimento sobre a formação de simbiose na planta de interesse. Desta forma objetivouse, neste estudo, verificar se plantas de B. cheilantha formavam simbiose micorrízica no campo e se havia variação entre os períodos seco e chuvoso. Após a confirmação da formação de simbiose micorrízica em plantas de B. cheilantha testou-se, em casa de vegetação, o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This result was not observed by Oliveira, Teixeira-Rios et al (2015), who reported a low correlation between mycorrhizal colonization and sporulation of these same isolates in baraúna. For Nascimento et al (2014), several abiotic factors can influence NG, such as soil type, humidity, pH, and temperature; however, Violi et al (2007) emphasized that the interaction between plant species and fungal isolates are also determinants in sporulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was not observed by Oliveira, Teixeira-Rios et al (2015), who reported a low correlation between mycorrhizal colonization and sporulation of these same isolates in baraúna. For Nascimento et al (2014), several abiotic factors can influence NG, such as soil type, humidity, pH, and temperature; however, Violi et al (2007) emphasized that the interaction between plant species and fungal isolates are also determinants in sporulation.…”
Section: Resultsmentioning
confidence: 99%
“…(Teixeira-Rios et al, 2016), Brazilian orchid tree (pata-de-vaca) (Bauhinia forficata Link.) (Nascimento et al, 2014), among others. However, few studies have focused on the contribution of this symbiosis to the survival and development of native plants, mainly in the Caatinga biome (Maia et al, 2010).…”
Section: Introduction and Objectivesmentioning
confidence: 98%
See 1 more Smart Citation